PSYCHOLOGICAL FACTORS IN THE ADAPTATION OF TRAINEES TO A SIMULATION-BASED LEARNING ENVIRONMENT - Kravchenko, Oksana; Safin, Oleksandr; Mas, Nataliia (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2025)
B a c k g r o u n d . The adaptation process involves the simultaneous and multidirectional influence of a range of both subjective and objective factors. One of the objective indicators of successful adaptation is the accurate execution of assigned tasks. Accordingly, this study includes an evaluation of the effectiveness of manipulations performed with simulation equipment.M e t h o d s . The study employed: an author's questionnaire for in-depth assessment of attitudes toward training in a simulation environment and interpersonal relationships within this context; the "Dominant State" methodology; the Multilevel Personality Questionnaire "Adaptability"; the Big Five Personality Inventory "BIG 5"; the KON-2006 Questionnaire; the Achievement Motivation Test and the "Motivation to Avoid Failure" Questionnaire. R e s u l t s . The study identified several distinctive features in how trainees perceive simulation-based training. The primary factor influencing this perception is the practical experience they acquire. Trainees recognise its significance and acknowledge its critical role in mastering training in a simulated setting. The second most prominent factor relates to the characteristics of the specific simulation equipment. This suggests that modifications to the system of interaction with instructors could further unlock the potential of simulation-based training. Trainees emphasise the need to adapt and improve engagement with instructors to optimise learning opportunities. The third factor concerns the constraints and nuances of interaction with the simulator itself. The possibilities and limitations associated with the use of simulators can significantly affect both the perception and effectiveness of training within the simulated environment.C o n c l u s i o n s . Based on the results of thematic analysis, five thematic domains were identified, reflecting key aspects of cognitive and mental representation of training in a simulation-based environment: physical (technical), psychological, and social components, as well as both positive and negative attitudes. Taking into account the findings – which allowed for the identification of specific stressors associated with simulationbased learning – a multidimensional follow-up study on the adaptation process is planned, along with the development of a psychological support system for trainees.
Keywords: adaptation process; internal and external factors; simulation equipment; manipulations; adaptive activity; trainees; task performance efficiency; individual psychological traits